2021
DOI: 10.1101/2021.04.06.438606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hda1C restricts the transcription initiation frequency to limit divergent non-coding RNA transcription

Abstract: Nucleosome-depleted regions (NDRs) at gene promoters support initiation of RNA Polymerase II transcription. Interestingly, transcription often initiates in both directions, resulting in an mRNA, and a divergent non-coding (DNC) transcript with an unclear purpose. Here, we characterized the genetic architecture and molecular mechanism of DNC transcription in budding yeast. We identified the Hda1 histone deacetylase complex (Hda1C) as a repressor of DNC in high-throughput reverse genetic screens based on quantit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Image analysis smFISH spot segmentation was performed on the maximum intensity projections. RNA smFISH spots were identified by fitting to a 2D Gaussian mask and performing local background subtraction using custom python code adapted from Donovan et al (2019) and Gowthaman et al (2021). Cytoplasmic and nuclear masks were generated using Cellprofiler (Carpenter et al, 2006).…”
Section: Sequential Smfishmentioning
confidence: 99%
“…Image analysis smFISH spot segmentation was performed on the maximum intensity projections. RNA smFISH spots were identified by fitting to a 2D Gaussian mask and performing local background subtraction using custom python code adapted from Donovan et al (2019) and Gowthaman et al (2021). Cytoplasmic and nuclear masks were generated using Cellprofiler (Carpenter et al, 2006).…”
Section: Sequential Smfishmentioning
confidence: 99%
“…Here, we showed that RSC is important to position nucleosomes and to ensure that cryptic divergent promoters are “protected” and transcriptionally repressed. Conversely, opening of chromatin because of increased histone lysine 56 acetylation (H3K56ac) leads to more divergent transcription in yeast, whereas deacetylation of histone H3 by Hda1 deacetylase complex (Hda1C) facilitates repression of divergent transcription ( Marquardt et al, 2014 ; Gowthaman et al, 2021 Preprint ). The GRF Rap1 can repress divergent transcription at gene promoters by occupying cryptic divergent promoters ( Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Divergent transcription units are also typically short, because of enrichment in transcription termination signals ( Schulz et al, 2013 ). In addition, divergent transcription can be repressed by chromatin remodellers and histone-modifying enzymes ( Marquardt et al, 2014 ; Gowthaman et al, 2021 Preprint ). Lastly, general regulatory factors (GRFs) can repress initiation of aberrant noncoding transcription events ( Challal et al, 2018 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased histone lysine 56 acetylation (H3K56ac) leads to more divergent transcription in yeast (Marquardt et al, 2014). Conversely, deacetylation of histone H3 by Hda1 deacetylase complex (Hda1C) facilitates repression of divergent transcription (Gowthaman et al, 2021). The role of RSC at promoters is likely different from CAF-I, H3K56ac, and Hda1C.…”
Section: Model For Promoter Directionalitymentioning
confidence: 99%
“…Divergent transcription units are also typically short, due to enrichment in transcription termination signals (Schulz et al 2013). Additionally, divergent transcription can be repressed by chromatin remodellers and histone modifying enzymes (Gowthaman et al 2021, Marquardt et al 2014). Lastly, general regulatory factors (GRFs) can repress initiation of aberrant noncoding transcription events (Challal et al 2018, Wu et al 2018).…”
Section: Introductionmentioning
confidence: 99%